Energy efficiency hybrid power management of electric vehicle (EV) charging through photovoltaic (PV) and micro grid (MG) - Rubini, B; Krishnakumar, R (International Journal of Engineering and Technology, 2018)
To Analyze wireless charging system of solar PV, panel concept with electric vehicle (EV). In this developed type is a combination of solar photovoltaic (PV) and Micro grid. In this type, designed two type of operation initially the EV Charging with micro grid input supply and PV Panel. If any fault occur or grid power failure the EV battery system charge through PV panel ultimately the battery sys-tem always on line charging either grid source or PV arrays panel. The proposed methods are integrated with bidirectional converter back-to-back converter with grid source. This paper focus into the power enhancement depends upon the irradiation of solar panels, so that the conversion of electrical energy is in accordance with the needs of electric vehicle attain maximum as possible. The design type of EV wireless charging methodology analyzed using MATLAB/Simulink is to get the effective power enhancement and charging to the electric vehicle continuous on line charging system.Â Â